Nursing & parental perceptions of neonatal care in Central Vietnam: a longitudinal qualitative study - Katie Gallagher; Colin Partridge; Hoang T Tran; Suzanna Lubran; Duncan Macrae (BMC, 2017)
Abstract Background Neonatal mortality accounts for nearly three quarters of all infant deaths in Vietnam. The nursing team are the largest professional group working with newborns, however do not routinely receive neonatal training and there is a lack of research into the impact of educational provision. This study explored changes in nursing perceptions towards their role following a neonatal educational intervention. Parents perceptions of nursing care were explored to determine any changes as nurses gained more experience. Method Semi-Structured qualitative interviews were conducted every 6 months over an 18 month period with 16 nurses. At each time point, parents whose infant was resident on the neonatal unit were invited to participate in an interview to explore their experiences of nursing care. A total of 67 parents participated over 18 months. Interviews were conducted and transcribed in Vietnamese before translation into English for manifest content analysis facilitated by NVivo V14. Results Analysis of nursing transcripts identified 14 basic categories which could be grouped (23) into 3 themes: (1) perceptions of the role of the neonatal nurse, (2) perception of the parental role and (3) professional recollections. Analysis of parent transcripts identified 14 basic categories which could be grouped into 3 themes: (1) information sharing, (2) participation in care, and (3) personal experience. Conclusions Qualitative interviews highlighted the short term effect that the introduction of an educational intervention can have on both nursing attitudes towards and parental experience of care in one neonatal unit in central Vietnam. Nurses shared a growing awareness of their role along with its ethical issues and challenges, whilst parents discussed their overall desire for more participation in their infants care. Further research is required to determine the long term impact of the intervention, the ability of nurses to translate knowledge into clinical practice through assessment of nursing knowledge and competence, and the impact and needs of parents. A greater understanding will allow us to continue to improve the experiences of nurses and parents, and highlight how these areas may contribute towards the reduction of infant mortality and morbidity in Vietnam.